A new threatened New Caledonian Leichhardtia (Apocynaceae, Asclepiadoideae, Marsdenieae) species discovered from a TV programme and social media - Gâteblé, Gildas; Meve, Ulrich; Liede-Schumann, Sigrid (Phytotaxa, 2023)
Just a few months after the publication of the Flore de la Nouvelle-Calédonie treatment for Asclepiadoideae, Periplocoideae and Secamonoideae, an unknown plant species obviously belonging to the genus Leichhardtia R.Br. was spotted while watching the local Wéari television programme on Caledonia channel and made available on YouTube. The focus of the TV programme was the remote and difficult to access Yandé island, in the extreme north of New Caledonia’s Grande Terre. Since few botanical investigations have been undertaken on this isolated island, the Wéari programme was an opportunity to get a better overview of its natural environment and plants. Here, we describe this Leichhardtia species and name it after this TV programme. Leichhardtia weari Gâteblé, Meve & Liede, sp. nov. is a narrowly endemic species with whitish flowers that is growing on serpentinite derived soils and known from less than ten individuals. Due to anthropogenic fire threat and its obvious rarity, we propose to consider it as Critically Endangered. In addition, a nomenclatural problem is fixed by proposing the new combination Leichhardtia guillauminiana (P.T.Li) Gâteblé, Meve & Liede, comb. nov; and a key for the now 20 species of Leichhardtia native to New Caledonia is presented.